DESAIN MASKOT GENI IKON BADAN PERPUSTAKAAN DAN KEARSIPAN SUMATERA BARAT - Juwita Wirta Sri Depi; Ahmad Akmal; Budiwirman Budiwirman (Ranah Seni, 2018)
Mascot Geni is the visual icon which gives design for visual communication to make reading interested to go to the Library and Archival of Sumatera Barat. Design a Mascot Geni is illustrated with book anatomy, deta and shoe. Book as body of Maskot Geni has meaning as science, then deta in the head has meaning as thought symbol and culture of Minangkabau. Last, shoe has meaning that tell reading is the fun adventure which is from one book to another books. In the way to create Mascot Geni is made by doig research of observation methodology, technic of collected data which makes, thr writer went to the library and archival of Sumatera Barat. Then, interviewed were conducted with head of service division in the Library and Archival Sumatera Barat. Documentation ti get data from books that has relevant, journal and picture. After that, Mascot Geni can be used as media for Billboard, X Banner, Sticker, Calender, Flax Change, T-Shirt, Clock and Mug. Eight of the media can support to promote Mascot Geni which persuade society especially children and teenager to come to the Library and Archival of Sumatera Barat.